„Prze-pisywanie” w literaturze najnowszej. Upominanie się o kobiece prawa w antologii "Ziarno granatu": Standing up for women’s rights in the collection Ziarno granatu - Wieczorek, Lidia (Acta Neophilologica, 2023)
Retelling and reinterpreting myths is one of the most popular literary devices of feminist criticism. In the anthology Ziarno granatu Polish authors reinterpreted individual Greek myths. The (re)telling of well-known myths from the female perspective emphasized the oppressive nature of these tales, showing how women were overlooked and discriminated against. The stories included in the anthology point to the timelessness of the issues of Greek myths, and the authors of the works indicate the correlations between ancient stories and contemporary Poland.